Early term delivery is associated with increased neonatal respiratory morbidity. Issue 1 (19th January 2021) - Bulut, Ozgul; Buyukkayhan, Derya
Abstract: Background: The recent increase in early term birth rates represents a growing challenge to public health given the association between early term birth and neonatal morbidities. We compared the risk of respiratory morbidity between early term and full‐term infants. Methods: This retrospective cohort population study included infants born at 37–41 weeks' gestation in a single tertiary care university hospital between 2014 and 2016. Newborns were categorized as early term (37–38 weeks) and full term (39–41 weeks). The primary outcome was respiratory morbidity. Results: Of the 4, 894 babies born at 37–41 weeks gestational age, 31% ( n = 1, 521) were early term births. The rate of cesarean deliveries, which were often elective, was higher for early term than for full‐term newborns ( P = 0.001). Compared with full‐term newborns, early term newborns, had significantly higher risks of respiratory morbidity (13.2 % vs 6.3 %; odds ratio [OR], 2.28, P = 0.001), respiratory distress syndrome (0.5 % vs 0 %, P = 0.001), transient tachypnea of the newborn (11.2 % vs 4.6 %; OR, 2.72, P = 0.001), continuous positive airway pressure use (9.7 % vs 3.7 %; OR, 2.82, P = 0.001), and ventilation support (1.4% vs 0.4%; OR, 4.11, P = 0.001). Conclusions: The elevated frequency of respiratory morbidity in early term infants emphasizes the importance of early term birth interventions. More than half of the early term births were elective cesarean sections; interventions should therefore focus on reducing elective cesarean procedures at the time of first birth.